(untitled) (Pedagogy of Higher and Secondary Education, 2006)
The article coven пен requirements to training of future music teacher in the system of higher education. The article highlights the essence and structure of competence art offuture music teacher, peculiarities of its formation in the process of training the fortepiuno playing.